ANALISIS LITERASI PENGELOLAAN KEUANGAN ISLAM PARA PEDAGANG KECIL DI KECAMATAN CILAWU KAB. GARUT - Ira Siti Rohmah Maulida; Arif Rijal Anshori; Iwan Permana; Neng Dewi Himayasari (ITB AAS Indonesia Surakarta, 2023)
Abstrak - Most of the small traders in Cilawu Garut Subdistrict are ensnared by loan sharks (emok banks), this condition is due to limited literacy and legal sources of capital. The above phenomena really attract our attention to provide concrete solutions to small traders in Cilawu Subdistrict, Garut Regency in the form of Islamic financial management training. This service program is carried out for seven small traders from seven villages in Cilawu District who will provide a solution to the problem by being provided with assistance in implementing Islamic financial management for two months and given a certificate as a mark of graduation and deemed worthy of having the ability in managing Islamic finance. The results are that Islamic financial literacy in small traders in Cilawu District, Garut Regency is not literate or does not yet have knowledge and confidence in financial service institutions and financial products and services which is shown from the results of interviews with small traders using their capital from moneylenders. So that there is a need for education regarding Islamic financial literacy which includes understanding and habits regarding the basics of Islamic financial literacy also influencing the behavior of business owners in running a business in accordance with Islamic economic rules and ethics and introducing Islamic financial service institutions that are able to help provide capital for traders.